ACTIVITY OF AQUEOUS ETHANOL EXTRACT OF EUPHORBIA SCORDIFOLIA ON SHIGELLA DYSENTERIAE TYPE 1-INDUCED DIARRHEA IN RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Euphorbia scordifolia is traditionally used in Cameroon for the treatment of many diseases, including diarrhea. We investigated the effect of the aqueous ethanol extract of Euphorbia scordifolia (EWES) on intestinal propulsion, bacterial in vitro growth and in vivo shigellosis. To value effects of EWES on intestinal propulsion, normal rats orally received 0, 50, or 75 mg/kg bw extract and the distance covered by the charcoal meal was measured. Shigellosis was induced by oral administration of 1.2 × 109 Shigella dysenteriae type A1 (Sd1) to the rats. Diarrheic rats were treated for 6 days with 50, 75 mg/kg EWES or 20 mg/kg norfloxacin. Nitric oxide (NO) production in blood and in colonic homogenate; blood parameters, diarrheal stool weight and Sd1 density were assessed, and death rate recorded. In vitro, the minimal inhibitory and minimal bactericidal concentrations of EWES were 4000 and 12000µg/mL respectively. EWES significantly (P<0.01) reduced intestinal transit, bacterial growth, diarrheal stool weight and decreased NO production in large intestine (P<0.01). The results suggest that Euphorbia scordifolia possesses bactericidic and antidiarrheic properties, and could be a therapeutic alternative for diarrhea of bacterial etiology.